Effects Of Largest Shareholders On Dividend: A Study On Malaysian Firms - Yeo , Jeng Fatt (2015)
The purpose of this study is to identify the effects of the largest shareholder (LO) and the second largest shareholder (LO2) on the dividend policy in Malaysian firms.